Technologies of higher education institutions as a component part in an educational subsystem of developing the future specialist‟s general cultural competence in socionomy field - Olena Homoniuk (Vasyl Stefanyk Precarpathian National University, 2017)
The current situation encourages the specialists in socionomic sphere (teachers,psychologists, managers, lawyers) to move from adaptive activities oriented to the present dayto the creative ones oriented to the future. Technologies of higher education institutions are acomponent part in an educational subsystem of forming and developing the future specialist'sgeneral cultural competence. They promote the initial creation of the professional backgroundfor the skills development, gradual formation of the theoretical and practical readiness andthe possibility to carry out professional activities. Our article is dedicated to the peculiaritiesof using technologies of the development of the future specialist's general cultural competencein socionomy field as a component part of the professional pedagogical culture. Key words: technologies, general cultural competence, a specialist in socionomy field.